The effect of the COVID-19 pandemic on consumption and indirect tax in Ireland - Cathal Coffey; Karina Doorley; Conor O'Toole; Barra Roantree (The Economic and Social Research Institute (ESRI), 2020)
Using micro data from the Central Statistics Office (CSO) Household Budget Survey (HBS), we assess the effect of the COVID-19 pandemic on consumption and its implications for indirect tax receipts in 2020. We show that over one-third of household expenditure is on items that are currently restricted due to public health measures such as transport, selected retail expenditure and entertainment items. We parameterise three scenarios which attempt to take into account: 1) a return to a 'new normal' with ongoing physical and social distancing; 2) a 'second wave' lockdown; and 3) rapid vaccine development that allows a return to normal economic and social life by the end of 2020. Under these scenarios, household consumption this year is estimated to be between 12 and 20 per cent lower than what it would have been in the absence of the pandemic. Indirect tax paid by households is estimated to be between 19 and 32 per cent lower than it otherwise would have been.
Keywords: 330; Coronavirus; Privater Konsum; Indirekte Besteuerung; Prognose; Irland